Potensi Ekstrak Daun Kelor (Moringa oleifera) sebagai Agen Priming pada Performa Perkecambahan Biji Bawang Merah - Katriani Mantja; Muhammad Faried; Elkawakib Syam'un (Jurnal Ilmu Pertanian Indonesia, 2023)
Moringa leaf extract is a biostimulant containing various phytohormones that can spur plant growth and development. This study aimed to evaluate the potential of Moringa leaf extract as a priming agent on the germination performance of shallot seeds. The experiment began with leaf extract preparation, seed priming, and germination testing. The data obtained were analyzed using ANOVA, and if there was a significant effect, further tested with the BNJ test with α = 0.05. The data were processed using RStudio software version 4.2.1. The results stated that seed priming with leaf extract concentration of 37.5% had the best effect on all germination parameters, including average germination time (2.19 days), final germination percentage (96.53%), seed germination uniformity (95.83%), germination velocity coefficient (45.85), germination rate index (50.48%/day), sprout vigor index I (790.58), sprout vigor index II (31.30), plumula length (6.53 cm), radicle length (1.66 cm), sprout fresh weight (0.32 g), and sprout dry weight (0.0233 g). It was concluded that Moringa leaf extract has the potential as a priming agent for shallot seeds. Keywords: botanical seed, moringa leaf, priming, shallot